Facilitating redox kinetics of sulfur species by cobalt-nitrogen co-doped porous hollow carbon for high-performance Li-S battery. Issue 5 (May 2021) - Liu, Bihan; Wu, Zilong; Ismail, Nadia; Chen, Zhuo
Abstract: The shuttle effect of polysulfides is the main obstacle restricting the development of lithium-sulfur batteries. However, most efforts focused on physical adsorption and polar adsorption cannot fundamentally solve the problem of sluggish conversion of polysulfides, especially for high sulfur loading. Herein, a cobalt-nitrogen co-doped porous hollow carbon sphere (Co-CN) is synthesized in one step. The porous conductive carbon spheres can realize a rapid charge transfer, mitigate volume expansion during cycling and enhanced physical adsorption for polysulfides. Nitrogen and cobalt doping provide chemisorption and catalysis for the restriction and conversion of polysulfides. Furthermore, liquid Li2 S8 polysulfide was used as sulfur source to guarantee high sulfur loading and fast redox kinetic. Benefiting from the triple effect of physical adsorption, chemical adsorption and catalysis, the Co-CN@Li2 S8 cell with sulfur loading of 5.15 mg cm −2 delivers a high reversible initial capacity of 1499 mAhg −1 at 0.1C and 880.9 mAhg −1 after 100 cycles. More excitingly, the capacity decay rate was only 0.012% per cycle at 1C over 1000 cycles, indicating excellent long cycle stability. This work provides a facile and effective route for Co-CN as a sulfur host in lithium-sulfur battery.